Matrilineal Marriage System in AR Rizal’s Novel Limpapeh: A Literary Socio-anthropology Study - Zulfitriyani, Zulfitriyani; Fahruddin, Fahruddin; Sari, Reno Wulan (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research is motivated by the existence of a unique marriage system in the matrilineal tradition in Minangkabau society which is found in local Minangkabau color novels. Based on this background, this research examines the form of marital relations in local color novels in Minangkabau as a matrilineal tradition. The novel studied in this research is the novel Limpapeh by AR Rizal. Regarding the matrilineal marriage system, it is worth researching because since the era of modern literature in Indonesia, Minangkabau literature has been famous for ironic stories related to marriage and customs. After reform through his novel, AR Rizal displays the current state of society with a marriage system that still maintains the system of the past and is still often found in the reality of today’s society even though it is only expressed in the form of works of fiction. This research is a qualitative research using the content analysis method. The results of this research show that the forms of the marriage system in the novel Limpapeh by AR Rizal are marriages within the tribe, marriages outside the tribe, and marriages using the traditional system of collecting money. These three things are unique to Minangkabau traditions and customs which are still maintained today and are expressed in novels as literary works. The benefits of this research are theoretically useful for multidisciplinary research in literary research, namely studying literary anthropology as a combination of literary science, sociology and anthropology. Practically it can be a reference for other researchers and a further basis for further research.